Mixed carbonate–siliciclastic tidal sedimentation in the Miocene to Pliocene Bouse Formation, palaeo‐Gulf of California. Issue 3 (2nd January 2021) - O'Connell, Brennan; Dorsey, Rebecca J.; Hasiotis, Stephen T.; Hood, Ashleigh V. S.
Abstract: Mixed carbonate–siliciclastic deposits provide unique insights into hydrodynamic processes that control sedimentation in tidal systems. This study presents sedimentological and ichnological data from the upper Miocene to lower Pliocene Bouse Formation, which accumulated during regional transgression at the margin of a tidal strait near the north end of the ancestral Gulf of California. The basal carbonate member of the Bouse Formation records deposition in a tide‐influenced, compositionally mixed carbonate–siliciclastic system dominated by salt marsh, tidal flat and channel environments. The basal carbonate member is an overall deepening up succession of facies associations comprising: Facies Association 1 – siliciclastic‐rich heterolithic facies, lime mudstone with desiccation cracks, and plant debris rich carbonate silt interpreted as siliciclastic‐rich tidal flats; Facies Association 2 – well‐sorted gravels, siliciclastic‐rich sandy strata, lime mudstone with desiccation cracks, and sandy microbial micrite interpreted as tidal‐channel deposits; Facies Association 3 – carbonate‐rich heterolithic lime mudstone to well‐sorted, cross‐bedded bioclastic grainstone interpreted as intertidal to shallow subtidal deposits; and Facies Association 4 – lime mudstone interpreted as shallow to deep subtidal low‐energy deposits that record the end of tidal conditions in the basin. Trace fossils include marine forms Gyrolithes, Teichichnus and Thalassinoides, and non‐diagnostic forms Arenicolites, Cochlichnus, Conichnus, Lockeia, Planolites, Skolithos and Treptichnus (known from marine, brackish and freshwater environments). The diminutive size of trace fossils reflects brackish conditions created by mixing of freshwater and seawater. This study provides evidence for a late Miocene to early Pliocene humid climate in south‐western North America, in stark contrast to the modern hyperarid climate. Factors that controlled the relative percentage of mixed carbonate and siliciclastic sediment include siliciclastic input from local rivers, in situ carbonate production, current energy, degree of tidal mixing and relative sea level. Pronounced facies variability at bedform, outcrop and basin scale documented in this study appears to be an important characteristic of mixed carbonate–siliciclastic deposits in tidal depositional systems.